2020
DOI: 10.1186/s12889-020-09774-3
|View full text |Cite
|
Sign up to set email alerts
|

Gridlock from diagnosis to treatment of multidrug resistant tuberculosis (MDR-TB) in Tanzania: patients’ perspectives from a focus group discussion

Abstract: Background Molecular diagnostics have revolutionized the diagnosis of multidrug resistant tuberculosis (MDR-TB). Yet in Tanzania we found delay in diagnosis with more than 70% of MDR-TB patients having a history of several previous treatment courses for TB signaling prior opportunities for diagnosis. We aimed to explore patients’ viewpoints and experiences with personal and socio-behavioral obstacles from MDR-TB diagnosis to treatment in an attempt to understand these prior findings. Methods The study was co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 20 publications
1
8
1
Order By: Relevance
“…A study in India found that HCWs were not properly incentivised to work in the area of MDR/RR-TB, considering the difficult working environment and risk of being infected [26]. HCWs in our study also reported difficulty in hiring MDR/RR-TB staff and their perceived need of more training on MDR-TB, which echoes studies in other countries reporting a lack of knowledge in HCWs, even misconduct of HCWs who charge additional fees from patients [27,28]. In addition, our study reveals a lack of coordination mechanisms between the HCWs in the MDR-TB and other departments, further exacerbating the difficulties created by understaffing.…”
Section: Provider-side Obstaclescontrasting
confidence: 41%
“…A study in India found that HCWs were not properly incentivised to work in the area of MDR/RR-TB, considering the difficult working environment and risk of being infected [26]. HCWs in our study also reported difficulty in hiring MDR/RR-TB staff and their perceived need of more training on MDR-TB, which echoes studies in other countries reporting a lack of knowledge in HCWs, even misconduct of HCWs who charge additional fees from patients [27,28]. In addition, our study reveals a lack of coordination mechanisms between the HCWs in the MDR-TB and other departments, further exacerbating the difficulties created by understaffing.…”
Section: Provider-side Obstaclescontrasting
confidence: 41%
“…Patient and public involvement Development of this protocol was informed by a series of research studies that included one study that examined patients' experience of health services in the health facilities. 8 Findings from the described research objectives will be shared with patients' organisations for further refinement before subsequently contributing in shaping the agenda of effective integration of communicable and NCDs for policy-makers.…”
Section: Study Areamentioning
confidence: 99%
“…4 This sobering fact has been illuminated in Tanzanian research studies that uncovered a health system gridlock largely contributed by limited resources and skills-training for front-line healthcare providers, and weak linkage to other health services with the subsequent effect of underuse of technologies. [5][6][7][8][9] Likewise, the prevalence of dual communicable and NCD epidemics is increasing, yet communicable clinics are unprepared to deal with dual services. 10 11 For instance, the prevalence of diabetes mellitus (DM) ranged 4%-17% and hypertension ranged 7%-25% in people leaving with HIV attending clinics in Tanzania cities, while, in other settings within Tanzania, the prevalence of DM ranged 4%-5% and hypertension ranged 22%-30%.…”
Section: Introductionmentioning
confidence: 99%
“…The later regimens accommodate new anti-TB medicines such as bedaquiline, delamanid or pretomanid and repurposed anti-TB medicines that include clofazimine and linezolid. Various reports in Tanzania have shown multitude of implementation barriers and bottlenecks including limited knowledge of healthcare workforce, delay in diagnosis of RR-TB/MDR-TB, patients receiving multiple episodes of TB treatment and non-difference in final treatment outcomes in patients diagnosed with new technologies 9–11. Without addressing the implementation barriers, new technologies including new drugs might not improve the treatment outcomes and therefore WHO suggested that in resource-limited setting, adapting new second-line anti-TB regimen be implemented under pragmatic research approach 9…”
Section: Introductionmentioning
confidence: 99%
“…Tanzania is one of the countries that developed a pragmatic protocol and is implementing an injectable-free regimen protocol titled as ‘Removed Injectable modified Short—course regimens for EXpert Multidrug Resistant Tuberculosis’ (RISE study). Key changes in the MDR-TB regimen include substitution of injectable agents with bedaquiline and prioritised levofloxacin and linezolid as described elsewhere 9 10. The RISE study is a prospective open-label cohort continuously enrolling eligible patients (patients with newly diagnosed pulmonary MDR-TB) measuring uptake (enrolment), 6-month conversion, serious adverse events treatment results at 9 months (primary end point) and relapse and death during a follow-up period of 12 months (secondary end point).…”
Section: Introductionmentioning
confidence: 99%